DACAmented in the age of deportation: navigating spaces of belonging and vulnerability in social and personal live. Issue 1 (2nd January 2020) - Gonzales, Roberto G.; Brant, Kristina; Roth, Benjamin
ABSTRACT: Heightened immigration enforcement in public spaces has brightened the boundaries of exclusion for undocumented immigrants in the United States. Yet, these immigrants simultaneously experience belonging and inclusion within the personal and social spheres of their lives. This article explores this tension among young people with Deferred Action for Childhood Arrivals (DACA). Drawing on interviews with 408 DACA beneficiaries in six states, our analyses underscore the significance of personal and social spheres as spaces of belonging. DACA expanded these spaces, helping respondents derive meaning, agency, and membership in their everyday lives. However, these personal and social spheres were at times disrupted by hostile and exclusionary contests to function as spaces of vulnerability. Respondents experienced the boundaries between belonging and vulnerability as unstable and, at times, ambiguous-as they navigated a state of social liminality. Ultimately, conflicting sociopolitical climates at the national, state, local and institutional levels have created this social liminality.